The Rural Household Multiple Indicator Survey, data from 13,310 farm households in 21 countries - Wijk, Mark T. van; Hammond, James; Gorman, Leo; Adams, Sam; Ayantunde, Augustine A.; Baines, David; Bolliger, Adrian M.; Bosire, Caroline K.; Carpena, Pietro; Chesterman, Sabrina; Chinyophiro, Amon; Daudi, Happy; et al. (Springer, 2020)
The Rural Household Multiple Indicator Survey (RHoMIS) is a standardized farm household survey approach which collects information on 758 variables covering household demographics, farm area, crops grown and their production, livestock holdings and their production, agricultural product use and variables underlying standard socio-economic and food security indicators such as the Probability of Poverty Index, the Household Food Insecurity Access Scale, and household dietary diversity. These variables are used to quantify more than 40 different indicators on farm and household characteristics, welfare, productivity, and economic performance. Between 2015 and the beginning of 2018, the survey instrument was applied in 21 countries in Central America, sub-Saharan Africa and Asia. The data presented here include the raw survey response data, the indicator calculation code, and the resulting indicator values. These data can be used to quantify on- and off-farm pathways to food security, diverse diets, and changes in poverty for rural smallholder farm households.